Malay version Stroke Knowledge Test - Sowtali, Siti Noorkhairina; Mohd Yusoff, Dariah; Harith, Sakinah; Mohamed, Monniaty (2019)
Malay version Stroke Knowledge Test is originally developed by Sullivan and Dunton (2004) as reported in their article "Development and validation of the Stroke Knowledge Test. Topics in Stroke Rehabilitation, 11(3), 19-28."